Use of some plant extracts as anticorrosive agents for aluminum in aqueous media - Reem Mohamed Mohamed Amer El-Setawy; Nabil Mahmoud Abd El-Monem; Hend El-Sayed Gadow (2025)
This study explores the corrosion inhibition efficiency of Swiss chard stem (SCS) and green pea peel (GPP) extracts as eco-friendly inhibitors on aluminum in 1 M HCl using weight loss (WL), potentiodynamic polarization, and electrochemical impedance spectroscopy techniques. Both inhibitors have a direct relation between the inhibition efficiency and the temperature. WL measurements revealed that at 250 ppm and 55°C, the inhibition efficiencies of SCS and GPP were 91.5% and 83.05%, respectively. Surface protection was validated by AFM and XPS analyses. Quantum chemical calculations identified the key inhibitory constituents, while molecular dynamics simulations revealed the adsorption behavior of SCS and GPP on aluminum. Extraction costs were evaluated and benchmarked against previously reported inhibitors.
1 . . 250 55 91.5% 83.05%. . . .
Thesis (M.Sc)-Cairo University, 2025.
Bibliography: pages 51-55.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Chemical Engineering; Corrosion Inhibition -- Swiss Chard Stem -- green pea peel -- Aluminum Surface -- Inhibition Efficiency